A Review of National and International Online Medical Systems - Carmen Catalina RUSU; Viorica BADEA; Luigi Renato MISTODIE; Costica VOICU (Modern Medicine)
Health and the access to medical services are key factors in the functioning of a sustainable society. In order to provide access to medical and health services, in the conditions of digitalization and implementation of ITC technologies, it is necessary to innovate and achieve synergies between digital and medical technologies. Digitization, innovation and research should be complementary fields that represent the engines of a modern digital economy. In this context, the main objective of this paper is to perform an analysis on the online medical systems, both nationally and internationally. This analysis aims to identify the technologies and tools for information and prevention, existing ICT products in the medical field and online medical platforms from Romania and abroad. The main aspects identified in the analysis will represent the premises for designing an innovative online platform, which will aim to increase the visibility of scientific information, facilitate access to medical materials and provide personalized digital medical services, created by members of the innovative cluster network „For Health Dunarea de Jos”, existing in the South-East region of Romania.